Phytochemical, Antidiabetic, Antioxidant, Antibacterial, Acute and Sub-Chronic Toxicity of Moroccan Arbutus unedo Leaves - Latifa Doudach; Hanae Naceiri Mrabti; Samiah Hamad Al-Mijalli; Mohamed Reda Kachmar; Kaoutar Benrahou; Hamza Assaggaf; Ahmed Qasem; Emad Mohamed Abdallah; Bodour Saeed Rajab; Khouloud Harraqui; Mouna Mekkaoui; Abdelhakim Bouyahya; et al. (Korean Pharmacopuncture Institute, 2023)
Objectives: Moroccan Arbutus unedo is an essential medicinal plant; however, little is known about the biological properties of its leaves mentioned in Moroccan traditional medicine.Methods : : Various standard experiments were performed to evaluate the phytochemical, antidiabetic, antioxidant, antibacterial, and acute and sub-chronic toxicity characteristics of A. unedo leaves.Results : : Phytochemical screening led to the identification of several phytochemical classes, including tannins, flavonoids, terpenoids, and anthraquinones, with high concentrations of polyphenols (31.83 ± 0.29 mg GAEs/g extract) and flavonoids (16.66 ± 1.47 mg REs/g extract). Further, the mineral analysis revealed high levels of calcium and potassium. A. unedo extract demonstrated significant antioxidant and anti-diabetic activities by inhibiting α-amylase (1.350 ± 0.32 g/mL) and α-glucosidase (0.099 ± 1.21 g/mL) compared to the reference drug Acarbose. Also, the methanolic extract of the plant exhibited significantly higher antibacterial activity than the aqueous extract. Precisely, three of the four examined bacterial strains exhibited substantial susceptibility to the methanolic extract . Minimum bactericidal concentration (MBC)/minimum inhibitory concentration (MIC) values indicated that A. unedo harbor abundant bactericidal compounds. For toxicological studies, mice were administered with A. unedo aqueous extract at single doses of 2,000 and 5,000 mg/kg. They did not exhibit significant abnormal behavior, toxic symptoms, or death during the 14-day acute toxicity test and the 90-day sub-chronic toxicity test periods. The general behavior, body weight, and hematological and biochemical status of the rats were assessed, revealing no toxicological symptoms or clinically significant changes in biological markers observed in the mice models, except hypoglycemia, after 90 days of daily dose administration.Conclusion : : The study highlighted several biological advantages of A. unedo leaves without toxic effects in short-term application. Our findings suggest that conducting more comprehensive and extensive in vivo investigations is of utmost importance to identify molecules that can be formulated into pharmaceuticals in the future.